EFFECTIVENESS OF SENSORY INTEGRATION INTERVENTIONS ON POSTURAL CONTROL DEVELOPMENT IN CHILDREN WITH AUTISM SPECTRUM DISORDER: AN EXPERIMENTAL STUDY - Mihaylov, Ivan (KNOWLEDGE - International Journal, 2026)
Postural control is a fundamental component of motor development, allowing children to maintain body stability and perform coordinated movements in everyday activities. Effective postural regulation relies on the integration of sensory information from the vestibular, proprioceptive, and visual systems. In children with Autism Spectrum Disorder (ASD), impairments in sensory processing often result in deficits in balance, coordination, and motor planning, which can negatively affect functional participation and motor performance. The aim of this experimental study was to evaluate the effects of sensory integration-based interventions on the development of postural control in children with ASD. Sixty children aged 4 to 7 years were included and randomly assigned to an experimental group (n=30) and a control group (n=30). The experimental group participated in a six-month therapeutic program combining sensory integration therapy with kinesitherapeutic balance training. The intervention included vestibular stimulation through swings and rotational activities, proprioceptive exercises aimed at enhancing body awareness, balance training on unstable surfaces, and functional movement tasks integrated into play-based activities. The control group received standard therapeutic support without structured sensory integration interventions. Postural control was assessed using a battery of motor tests evaluating static balance, dynamic balance, trunk stability, and bilateral coordination at three time points: pre-intervention, after three months, and at the end of six months. The results demonstrated significant improvements in the experimental group compared to the control group. Mean static balance scores increased by 32% (p < 0.01), dynamic balance by 28% (p < 0.01), and both postural stability and coordination showed significant gains (p < 0.05). Children who participated in the sensory integration program exhibited more efficient postural strategies and enhanced motor performance. These findings confirm that structured sensory integration interventions significantly improve postural control and motor function in children with ASD. The study emphasizes the importance of integrating sensory-based therapy with kinesitherapeutic approaches in pediatric rehabilitation to promote functional independence and motor development